Reintroducing Consciousness in Psychopathology: Review of the Literature and Conceptual Framework - Gert Ouwersloot; Jan Derksen; Gerrit Glas; Gerrit Glas (Frontiers in Psychology, 2020)
Alterations in consciousness are among the most common transdiagnostic psychopathological symptoms. Therefore clinical practice would benefit from a clear conceptual framework that guides the recognition, comprehension, and treatment of consciousness disorders. However, contemporary psychopathology lacks such a framework. We describe how pathology of consciousness is currently being addressed in clinical psychology and psychiatry so far, and how the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and International Classification of Diseases, Tenth Edition (ICD-10) refer to this subject. A brief review of the literature on consciousness is then given. After describing psychological perspectives on consciousness and discussing theoretical issues involved in exploring consciousness, we offer a practical clinical working definition of consciousness and we illustrate its connections with a variety of diagnoses. Making use of Jean-Paul Sartre’s distinctions among: states, functions, qualities, and structure, provide a conceptual framework to understand consciousness, to refine diagnostics and to guide the development of therapeutic possibilities in clinical practice.